Analysis of cyclin E co‐expression genes reveals nuclear transcription factor Y subunit alpha is an oncogene in gastric cancer. Issue 1 (1st March 2019) - Bie, Liang‐Yu; Li, Dan; Mu, Yu; Wang, Sheng; Chen, Bei‐Bei; Lyu, Hui‐Fang; Han, Li‐Li; Nie, Cai‐Yun; Yang, Chang‐Cheng; Wang, Lin; Ren, Chuan‐Chuan; Zhang, Wei‐Jie; et al.
Abstract: Objective: To explore genes potentially co‐expressed with cyclin E in gastric cancer and discover possible targets for gastric cancer treatment. Methods: The Cancer Genome Atlas (TCGA) stomach adenocarcinoma sequencing data were used to predict genes co‐expressed with cyclin E. Co‐expression genes predicted by cBioPortal online analysis with Pearson correlation coefficient ≥0.4 were analyzed by gene ontology (GO) enrichment annotation using the PANTHER online platform (Ver. 7). Interactions between proteins encoded by these genes were analyzed using the STRING online platform (Ver. 10.5) and Cytoscape software (Ver. 3.5.1). Genes displaying a high degree of connection were analyzed by transcription factor enrichment prediction using FunRich software (Ver. 3). The significant transcription factor and cyclin E expression levels and their impact on gastric cancer progression were analyzed by Western blotting and Kaplan–Meier survival curve analysis. Results: After filtering the co‐expression gene prediction results, 78 predicted genes that included 73 protein coding genes and 5 non‐coding genes with Pearson correlation coefficient ≥0.4 were selected. The expressions of the genes were considered to be correlated with cyclin E expression. Among the 78 genes co‐expressed with cyclin E, 19 genes at the central of the regulatory network associated with cyclin E were discovered. Nuclear transcription factor Y subunit alpha (NF‐YA) was identified as a significant transcription factor associated with cyclin E co‐expressing genes. Analysis of specimen donors' clinical records revealed that high expression of NF‐YA tended to be associated with increased cyclin E expression. The expression of both was associated with progression of gastric cancer. Western blotting results showed that compared with normal tissues, NF‐YA and cyclin E were highly expressed in tumor tissues ( P  < 0.001). Survival curve analysis clearly demonstrated relatively poor overall survival of gastric cancer patients with high cyclin E or high NF‐YA expression level, compared to patients with low cyclin E or NF‐YA expression ( P  < 0.05). Conclusions: NF‐YA may promote gastric cancer progression by increasing the transcription of cyclin E and other cell cycle regulatory genes. NF‐YA might be a potential therapeutically useful prognostic factor for gastric cancer.